Giant Morpheaform Basal Cell Carcinoma Mimicking Scarring Alopecia: Exception Prone to Neglect - Carlo Francesco Tomasini; Giacomo Fiandrino; Emanuele Mario Favale; Francesca Antoci; Stefania Barruscotti (MDPI AG, 2024)
A 74-year-old woman in good general health presented with a 5-year history of progressive hair loss over several years, interpreted as female androgenetic alopecia (AGA), and was treated with topical 5% Minoxidil without improvement. The patient's relevant medical history revealed infiltrating, triple-negative apocrine carcinoma of the right breast four years before, treated by quadrantectomy, radiation, lymphadenectomy and chemotherapy, with no recurrence at the last follow-up. On examination, there was an asymptomatic 15 × 15 cm firm and whitish area of scarring alopecia on the central scalp. Dermoscopy revealed multiple arborizing vessels and many telangiectasia. The clinical considerations included mainly cutaneous metastasis of breast carcinoma (alopecia neoplastica), pseudopelade of Broque and morpheaform basal cell carcinoma (BCC). A histopathologic examination revealed characteristic changes of morpheaform BCC with basaloid islands and cords of atypical basaloid cells diffusely infiltrating the dermis, embedded in a sclerotic and hypervascularized stroma. Secondary alopecia neoplastica due to morpheaform BCC on the scalp is an exceedingly rare entity, possessing subtle clinical features that may mimic both scarring and non-scarring alopecia. Delayed recognition may contribute to aggressive behavior and extensive local destruction. Treatment with hedgehog inhibitors in locally advanced BCC of the scalp, both in adjuvant and neoadjuvant modalities, is promising.